Frequency and importance of interpersonal communication about a school-based intervention with parents, peers, and teachers: application of social interface model. Issue 6 (2nd November 2021) - Shin, Young Ju; Pettigrew, Jonathan; Ray, Colter D.; Lu, Yu
ABSTRACT: Social interface model (SIM) explicates the important roles of family, peer, and school microsystems in intervention research. The present study used surveys to explore how Nicaraguan adolescents who participated in a school-based substance use and violence prevention intervention communicated about the intervention with parents, peers, and teachers. Latent class analysis was run to identify distinctive typologies of interfaces characterized by occurrence and importance of conversations. Five latent classes ( N = 109) were discovered: optimal transference (21%), neutral transference (17%), limited positive transference (17%), negligible neutral interface (28%), and negligible adverse interface (16%). The optimal transference and neutral transference groups reported having conversations with all three microsystems (i.e. their mother, father, best friend, and teachers) and that those conversations resulted in seeing the curriculum the same way or as more important. The negligible neutral interface and negligible adverse interface groups reported minimal or no conversation across microsystems, which resulted in viewing the curriculum as not important or less important. The limited positive transference group reported selective conversations mostly with their mother and teachers, which was evaluated as important and/or neutral. Findings discuss the application of SIM in prevention research and provide a more nuanced understanding of how intervention messages are recalled and processed post-delivery.